2010
DOI: 10.1103/physrevb.82.180407
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale chemical fluctuation inLaSrVMoO6, a proposed half-metallic antiferromagnet

Abstract: Half-metallic antiferromagnets ͑HMAFMs͒ have been proposed theoretically long ago but have not been realized experimentally yet. Recently, a double perovskite compound, LaSrVMoO 6 , has been claimed to be an almost real HMAFM system. Here, we report detailed experimental and theoretical studies on this compound. Our results reveal that the compound is neither a half-metal nor an ordered antiferromagnet. Most importantly, an unusual chemical fluctuation is observed locally, which finally accounts for all the el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…The reasons for this are not yet clear, but some seem to result from antisite disorder on B and B ′ sites. 15 In particular, in systems having 3d ions in both B and B ′ sites, similar ionic radii often prevent a well-ordered sample from being established, resulting in undermined compensation of magnetic moments. …”
mentioning
confidence: 99%
“…The reasons for this are not yet clear, but some seem to result from antisite disorder on B and B ′ sites. 15 In particular, in systems having 3d ions in both B and B ′ sites, similar ionic radii often prevent a well-ordered sample from being established, resulting in undermined compensation of magnetic moments. …”
mentioning
confidence: 99%
“…SrLaVMoO 6 with an ordered double perovskite has been 1237 suggested to be a HMAF state by considering antiparallel alignment of alternately occupied V 3+ (3d 2 ) and Mo 4+ (4d 2 ) spins at the B-site of the perovskite structure. However, a recent report on experimental studies of bulk polycrystalline SrLaVMoO 6 along with electronic-structure calculations [15] have suggested that an atomic-scale chemical fluctuation played an important role and should be incorporated in order to account for the electronic and magnetic properties of the compound. The authors proposed a picture of very local antiferromagnetic insulating LaVO 3 -and paramagnetic metallic SrMoO 3 -like regions to explain their x-ray absorption fine structure results on SrLaVMoO 6 with a completely disordered double perovskite structure.…”
Section: Introductionmentioning
confidence: 98%
“…A couple of reports claimed this system to be the first experimentally realized HMAFM, 6,7 while ab-initio band structure calculation results based on the experimental crystal structure opined otherwise, 8,9 confirming half-metallicity but predicting robust ferrimagnetic ground state for this compound. Therefore, quite contradictory depictions existed till our experiments 5 revealed the fact that the ground state of this compound is neither halfmetallic nor antiferromagnetic. Most importantly, our study showed that the local chemical , that might be present in a multi-cation system, needs to be considered while probing the structure and properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…But, the present study established that the most 'homogeneous' sample is indeed the one that we have already reported earlier. 5 Further, our theoretical calculation showed why this structure with chemical fluctuation has to be the most stable configuration for LaSrVMoO 6 ; where the driving force is the preference of La ions to form strong covalent linkages with the O ions that are linked to V ions, over the ones connected to Mo. The distinction arises due to the more ionic nature of V ions compared to Mo ions, finally resulting in La,V-rich, and the consequent Sr,Mo-rich regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation